Role of the nucleolus in neurodegenerative diseases with particular reference to the retina: a review. (5th February 2016) - Sia, Paul I; Wood, John PM; Chidlow, Glyn; Sharma, Shiwani; Craig, Jamie; Casson, Robert J
Abstract: The nucleolus has emerged as a key regulator of cellular growth and the response to stress, in addition to its traditionally understood function in ribosome biogenesis. The association between nucleolar function and neurodegenerative disease is increasingly being explored. There is also recent evidence indicating that the nucleolus may well be crucial in the development of the eye. In this present review, the role of the nucleolus in retinal development as well as in neurodegeneration with an emphasis on the retina is discussed.